Evaluation of the intellectual potential level at the enterprises of the real sector of the economy of Aktobe region - Sultanova, Z.Kh.; Ibyzhanova, A.D. (KSU Publ., 2017)
Success of innovative innovations in industrial enterprises, in spheres of economy and in economy in total depends on personnel and its professional level, since the primary purpose of modern knowledge-intensive management of production is assuring the effectiveness of the entity and its progressive development. That led to the choice of the level of intellectual potential in enterprise as the object of research. In this article theoretical and practical aspects of forming the level of intellectual potential in enterprises were considered. The article focuses on searching of the ways to improve the efficiency of human resources for enterprises' development. Object of research are some enterprises of the real sector of the economy of Aktobe region. Methodological framework for research comprises methods such as statistical method, index method, chain-linked approach, comparison method. It is proposed to use the intellectual indicator of the enterprise as an evaluation criterion. This indicator quantifies the intellectual potential of the collective, and shows the degree of its manifestation in conditions of its formation, use and development. The intellectual potential and results of activity of the enterprises of JSC «Aktyubinsk Oil Equipment Plant», JSC «AZHS», LLP «Aktyubinsk plant of metal structures» and LLP «Stern-IT» are compared. It has been established that LLP «Stern-IT» has the worst indicators. Specific measures to increase the intellectual potential of the company, such as are the introduction of a system of remuneration of labor in terms of competence; the introduction of a career planning system; stimulation of staff development are proposed.
Ақтөбе облысы экономикасының нақты секторы кəсіпорындарында зияткерлік əлеуетті бағалау факторларына баға
Оценка факторов уровня интеллектуального потенциала на предприятиях реального сектора экономики Актюбинской области
Keywords: potential; intellectual potential; career; salary; level of education; intellectual capital